(untitled) (Journal of Mathematical Study, 2020)
A C^2 function on R^n is called strictly (n-1)-convex if the sum of any n-1 eigenvalues of its Hessian is positive. In this paper, we establish a global C^2 estimates to the Monge-Ampère equation for strictly (n-1)-convex functions with Neumann condition. By the method of continuity, we prove an existence theorem for strictly (n-1)-convex solutions of the Neumann problems.